How does occupational radiation exposure affect corneal endothelial cell density? - Can, Mehmet Erol (The European Research Journal, 2019)
Objectives: To evalute the corneal endothelium ofradiology technicians.Methods: The study included 35 radiology technicians (study group), and 34 healthy individuals as the control group. Central corneal thickness (CCT), Endothelial cell density (ECD), the coefficient of variation (CoV), and the percentage of hexagonal cells (Hexa) were measured using specular microscopy (Konan Medical Inc., Nishinomiya, Japan). Results: The mean age of the study participants was 35.82 ± 9.34 years in the study group, and 37.82 ± 8.40 years in the control group (p = 0.332). The mean ECD was 2740.63 ± 249.92 cells/mm2 in the study group, and 2828.70 ± 287.40 in the control group (p > 0.05). The mean CoV was 44.34 ± 6.78 % in the study group, and 44.24 ± 4.99 % in the control group (p > 0.05). Hexa was determined as 44.97 ± 7.98% in the study group, and 45.97 ± 7.06% in the control group (p > 0.05). The mean CCT was 511.50 ± 42.52 in the study group, and 514.18 ± 43.55 in the control group (p > 0.05). The mean ECD, CoV, Hexa, and CCTvalues were not statistically significant (p > 0.05). Conclusion: This study revealed that endothelial cell density, the coefficient of variation, and percentage of hexagonal cells (Hexa) were not statistically different between the radiology technicians and control group. Nevertheless, there is a need for more comprehensive, controlled studies with larger samples.